(untitled) (Journal of the College of Basic Education, 2023)
Most of the definitions that dealt with the nature of globalization are ramified, multiple, and biased towardsThe problem is that the inevitability of controversy and debate about its borders, its area, and the different spacesBetween them, it gave the researchers space to interpret it based on their privacy and their mental and intellectual structures.and patterns of culture circulating in the knowledge markets. All these subjectivities indicate their perceptions in the mind.You come up with bewildered question marks, what does globalization mean? Especially in the context ofAwareness, culture and modes of communication, including theatre, are they universal in modern cultural structures? MotherIs it crossing the boundaries between what is local, national and global? Or is it a project to establish a cultureUnilateral inclusive and different from what is prevailing? Or is it imposing a pattern against a pattern? Or a modern civil struggleWith authentic civilizations, the awareness of its generations has accumulated over time as a text, so it is a conceptual approach to phenomena.Declared and hidden visions of the conscious and unconscious relationships between members of multiple societiesWithin the framework of one nation, whose methodologies and concepts have diversified despite the adoption of common rules.In founding and rooting, or is it an exchange of my interests between one culture and another while recognizing the rightEach of them has the continuity and riches according to the different hereditary sources and laws that are rooted in them.The local and national association.After these questions, how did the image, essence and surroundings of globalization appear in the mind of the citizen?The Arab in general and the intellectual in particular?If we dealt with the opinions of Arab intellectuals, we would come to the conclusion that, once again, there is a split in the mind.The Arab is giving rise to a new crisis in the Arab culture, the two sides of which are those who are compatible with the concepts ofIts images dazzled him, so he was joyful and, in the name of modernity, sided with an idea whose initial lines had not yet been completed.We only sense its characteristics through invitations, visions, and dissonant rhythms that floated over the roofs of magazines.and Arab newspapers, until the spectra and dreams of some of our intellectuals and waiters became a source of approval.its principles despite their lack of experience with the circumstances of its upbringing, and despite their stubbornness with themselves and others in their extremismAnd their bias towards it without awareness of what it will lead to tomorrow.